Formulasi dan Uji Kestabilan Fisik Lilin Aromaterapi Minyak Atsiri Bunga Melati (Jasminum sambac L) - Besse Yuliana; Andi Makkulawu; Annisa Ramadhani Amal (Journal Syifa Sciences and Clinical Research, 2023)
Aromatherapy candles are alternative medicine (inhalation) namely inhalation, aroma vapor produced form a few drops esensial oils. Jasmine flower (Jasminum sambac L.) is used widely as Aromatherapy for the manufacture of essential oils, generally brownish yellow in  color with the characteristic odor. Contains chemical compounds of jasmine oil, namely lynalol 10. 13%, nerolidol 19.95%, and indole 4. 05%. Jasmine Flower essential oil Aromatherapy candle (Jasminum sambac L.) This type oh the research was experimental, including physical burning point tests, melting point tests and hedonic tests. The results showed that the preparations had made white and yellow colors, different aromas according to the concentration of the essential oil, the melting point 52-59℃ according to the requirements according to SNI, namely 42-60℃, the fastest burning time was the old formula K(-), formula 2and 3 the fastest burning time, and in the hedonic test, formulation 3 was the most favored by the panelists and the K(-) formulation was less favored by the panelists. The conclusion oh this research is that jasmine essential oil (Jasminum sambac L.) can be formulated aromatherapy candles preparations, jasmine flower essential oil (Jasminum sambac L.) in aromatherapy candles is physical stable and jasmine essential oil aromatherapy candles  (Jasminum sambac L.) has high level of liking by the panelists.